2020
DOI: 10.3390/polym12061315
|View full text |Cite
|
Sign up to set email alerts
|

Particle Size Related Effects of Multi-Component Flame-Retardant Systems in poly(butadiene terephthalate)

Abstract: Aluminum tris-(diethylphosphinate) (AlPi) is known to have an efficient flame-retardant effect when used in poly(butadiene terephthalates) (PBT). Additionally, better flame-retardant effects can be achieved through the partial substitution of AlPi by boehmite in multi-component systems, which have been shown to be an effective synergist due to cooling effects and residue formation. Although the potential of beneficial effects is generally well known, the influence of particle sizes and behavior in synergistic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 37 publications
(55 reference statements)
0
1
0
Order By: Relevance
“…The test results revealed that 20wt% MCA and 10wt% ADP made the LOI value of epoxy resin increase from 19-33%, and UL 94 rating also changed from no rating to V-0 rating. Tomiak F et al [30] applied AlPi and boehmite in poly(butadiene terephthalates)(PBT). As compared to 20wt% ADP, 15wt% ADP and 5wt% boehmite were added to PBT showing better results, whose LOI value further raised from 49-53%, and the residual char also raised from 14wt% to 16wt%.…”
Section: Introductionmentioning
confidence: 99%
“…The test results revealed that 20wt% MCA and 10wt% ADP made the LOI value of epoxy resin increase from 19-33%, and UL 94 rating also changed from no rating to V-0 rating. Tomiak F et al [30] applied AlPi and boehmite in poly(butadiene terephthalates)(PBT). As compared to 20wt% ADP, 15wt% ADP and 5wt% boehmite were added to PBT showing better results, whose LOI value further raised from 49-53%, and the residual char also raised from 14wt% to 16wt%.…”
Section: Introductionmentioning
confidence: 99%